Assessment of spatial variability of some affecting parameters on water quality of Zarin Gol river in Golestan province - Mohammad Gholizadeh; Majid Alinejad (علوم محیطی)
Introduction: With the increase in population and more demand for agricultural and aquaculture activities the importance of water resource quality and quantity have increased and consequently surface water resources are faced with pollution more than other water resources. Generalizing point measurements of water quality characteristics to maps is of special significance in most water resources studies. Interpolation techniques may be used to estimate unknown parameter values. The aim of this study is to use the best interpolation method for water quality assessment of Zarin Gol River and the effect of different human activities. Materials and methods: For this purpose, samples were collected from 12 study stations in winter and spring of 2016. Then, the spatial variations of physical and chemical parameters of surface water were determined including DO, NO3, PO4, Turbidity, pH and TSS and Hilsenhoff index (water quality index) using interpolation functions based on cross validation technique (lowest value of RMSE, highest value of R2 and lowest close to zero values of spatial data MBE and MAE) of deterministic and geostatistical methods in GIS environment.  Results and discussion: The result showed that for all the studied parameters, kriging method was suitable compared to IDW and was selected for mapping. The result of modelling showed that the maximum value of Helsenhoff index was observed in stations 2 and 10 (5.31 and 5.2 respectively) in winter season with the relatively weak class in terms of water quality. The result of indices showed that stations were located after fish farm more pollution than their before stations and away from the farms have had the self-purification process. Conclusion: Investigation of special variations of environmental characteristics of water showed that increasing physical and chemical parameters of surface water along the river including wastewater discharge of villages, fish farms and agricultural activities have direct impact on water quality and pollution level increases and water quality decreases from up to down the river.